Antecedents of Job Satisfaction of Production Employees: Leadership, Compensation and Organizational Culture - Aldrin Arizona Suyono; Denny Oktavina Radianto; Damarsari Ratnasahara Elisabeth (IJEBD (International Journal of Entrepreneurship and Business Development), 2019)
Purpose: is to find out and analyze (1) the influence of leadership on job satisfaction of production employees, (2) the influence of compensation on job satisfaction of production employees, (3) the influence of organizational culture on job satisfaction of production employees, (4) the influence of leadership, compensation and organizational culture simultaneously on the job satisfaction of production employees. Design/methodology/approach: Analysis techniques using multiple linear regression using the F-test and t-test.. Sampling technique using random sampling techniques with a lottery system. Research limitations/implications: This research was conducted on industrial textile production employees in Nganjuk with a population of 800 production employees. The size of the sample is determined using the Slovin formula and got a sample of 89 Practical implications: The results of this research are (1) leadership had significant influence on on job satisfaction of production employees, (2) compensation had significant influence on on job satisfaction of production employees, (3) organizational culture had significant influence on on job satisfaction of production employees, (4) leadership, compensation and organizational culture simultaneously had significant influence on job satisfaction of production employees.. Originality/value: Paper type: This paper can be categorized as case study paper.